Metabolic Remapping at “Point‐Line‐Plane” Levels With Central Dysfunction in Cerebral Small Vessel Disease - Jie Ma; Juan‐Juan Lu; Xin Gao; Jia‐Jia Wu; Xiang‐Xin Xing; Mou‐Xiong Zheng; Xu‐Yun Hua; Jian‐Guang Xu (Brain and Behavior)
ABSTRACT Background This study is aimed at investigate the glucose metabolic patterns of cerebral small vessel disease (CSVD) at “point‐line‐plane” levels. Methods We retrospectively collected the 18F‐fluorodeoxyglucose PET/MRI images of 174 CSVD patients and 206 healthy controls. First, the brain FDG‐PET of each subject was divided into 7 classical networks, and the mean standard uptake value (SUVmean) was calculated. Second, the SUVmean of different brain networks was compared at the region of interest and voxel level. Third, the metabolic connectivity of intra‐ and inter‐networks was compared. Fourth, the correlation of SUVmean changes in different networks was calculated. Finally, the correlation between the SUVmean of the whole network and each brain region within the network was analyzed in different brain networks. Results Increased SUVmean was mainly shown in the right postcentral gyrus in the somatomotor network and the right superior parietal gyrus in the dorsal attention network; decreased SUVmean was predominantly observed in the right superior temporal gyrus in the somatomotor network in the CSVD group. Significant correlations of SUVmean alterations in varying networks and SUVmean of the whole network and each brain region within the network were found. Conclusion Affected by CSVD, the glucose metabolism redistribution is heterogeneous in different brain network, and its changes start from brain region and metabolic connectivity within the sub‐brain network.